(untitled) (Legal journal - Research in Legal and Social Sciences, 2023)
The present research makes an analysis of the implications of the special appeal recourse, with respect to the constitutional principles and international commitments assumed by the Republic of Paraguay. In this sense, the State ratified by Law n.° 1/89, the Pact of San José de Costa Rica, which implies an approach to the judicial guarantees established. For this purpose, a qualitative approach with a non-experimental design was used, as for the type is documentary, and the data collection technique was documentary analysis of the content, which was classified in a file. However, the current position of the Inter-American Court of Human Rights is that, regardless of the name of the appeal, there is a need to review the judgment in a comprehensive manner, that is, to address factual issues of the evidence. Indeed, it should be borne in mind that, in addition to considering the collision of the principle of immediacy, the violation of other established principles, such as the principle of double instance, is not superimposed. In short, it can be affirmed that it is necessary to study the wording of the current art. 467 of the Criminal Procedural Code, in relation to the current criterion of the Court with respect to the integral review of the judgment.